(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The Corporate Governanceensures the smooth and transparent functioning of the securities market. Thereare some norms which regulate the corporate governance of a particular company.The paper focuses to look at theevolution of these norms, its present status and the future and how conduciveit will be adopt these rules as mandatory governance norms for the IndianCorporate World. It has been an argument against mandatory corporate governancenorms, across the globe that not all well governed companies make profit andconversely not all bad governed companies sink either. The scope of the paper shall be limited to Corporate Governance inIndia; however necessary references (in terms of evolution of these norms) toposition in the United States of America and European Union shall be madewherever necessary. The paper shall deal with the different legal obligations like listingagreements, company law etc. required to be followed which ensure effective securitymarket. The paper shall also deal with the future possibilities and problems inthe Indian market. In the end, the paper shall also propose some suggestion and conclusion.